The Patients' Practises Disclosing Subjective Experiences in the Psychiatric Intake Interview - Savander, Enikö Èva; Hintikka, Jukka; Wuolio, Mariel; Peräkylä, Anssi (Frontiers in Psychiatry, 2021)
In psychiatric diagnostic interviews, a clinician's question designed to elicit a specific symptom description is sometimes met with the patient's self-disclosure of their subjective experience. In shifting the topical focus to their subjective experiences, the patients do something more or something other than just answering the question. Using conversation analysis, we examined such sequences in diagnostic interviews in an outpatient clinic in Finland. From 10 audio-recorded diagnostic interviews, we found 45 segments where medical questions were met with patients' self-disclosures. We show four sequential trajectories that enable this shift of topic and action. There are four possible trajectories: (1) the patient first answers the medical question and the clinician acknowledges this answer, whereupon the patient shifts to a self-disclosure of their subjective experience; (2) the patient first gives the medical answer but shifts to self-disclosure without the clinician's acknowledgement of that answer; (3) the patient produces an extensive answer to the medical question and, in the course of producing this, shifts into the self-disclosure; (4) the patient does not offer a medical answer but designs the self-disclosure as if it were the answer to the medical question. We argue that in the shifts to the self-disclosure of their subjective negative experience, the patients take local control of the interaction. These shifts also embody a clash between the interactional projects of the participants. At the end of the paper, we discuss the clinical relevance of our results regarding the patient's agency and the goals of the psychiatric assessment.